PENGARUH MODEL PEMBELAJARAN QUANTUM TEACHING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XI SMA NEGERI 1 PASAMAN - Setiawati, Xhosa Febrita (Jurnal Edukasi dan Penelitian Matematika, 2024)
The main purpose of learning mathematics is to improve one's ability to convey mathematical concepts to others through communication. Based on the preliminary findings of research conducted in class XI at SMA Negeri 1 Pasaman, the level of student ability in this domain is inadequate.  By using the Quantum Teaching (QT) teaching method can improve students' ability to express mathematical ideas. The objective of the research team at SMA Negeri 1 Pasaman was to evaluate the effectiveness of more traditional methods compared to the QT model in teaching mathematical communication to grade XI students. Based on quasi-experimental method, this study used a control group design limited to posttest. We used Simple Random Sampling technique for sampling. The result of the hypothesis test on both sample classes is ? value of 0.001. Students in grade XI of SMA Negeri 1 Pasaman who used the QT model had better abilities compared to students who used conventional methods. The QT model helps grade XI students at SMA Negeri 1 Pasaman in improving their ability to communicate mathematical ideas.Keywords–Mathematical Communication Skills, Quantum Teaching Learning Model, Conventional Learnin